Global Output-Feedback Prescribed Performance Control of Nonlinear Systems With Unknown Virtual Control Coefficients - Zhang, Jin-Xi; Wang, Qing-Guo; Ding, Wei (IEEE transactions on automatic control, 2022)
This article is concerned with the output-feedback tracking control problem for a class of nonlinear systems. The challenge lies in how to drive the tracking error to a prescribed region in a given time globally, under both unknown nonlinear functions and unknown virtual control coefficients. To deal with the unknown control direction, an orientation function is exploited in lieu of the Nussbaum gain technique, the supervisory switching strategy, and the parameter estimation approach. To attain global tracking performance, a tuning function is employed to adjust the tracking error, and a barrier function is used to combat this error. The resulting controller guarantees the prescribed tracking performance and the boundedness of the signals in the closed loop for any initial condition.